2021
DOI: 10.1210/clinem/dgab539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TSH Suppression Therapy on Bone Mineral Density in Differentiated Thyroid Cancer: A Systematic Review and Meta-analysis

Abstract: CONTEXT As subclinical hyperthyroidism increases the risk of osteoporosis and fractures, concerns are growing about the long-term skeletal safety of thyrotropin (TSH) suppression therapy after total thyroidectomy in patients with differentiated thyroid cancer (DTC). OBJECTIVE We aimed to determine the effect of TSH suppression therapy on bone mineral density (BMD) in DTC patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…[15] 2018 Spain Casecontrol 14 vs 84 1.00 ± 0.12 vs 0.98 ± 0.11, lumbar 14 vs 84 0.86 ± 0.12 vs 0.84 ± 0.15, lumbar 10 years BMD was higher among women with DTC who received thyroxine for TSH suppression, no difference in BMD was observed among males compared to their counterparts without TSH suppression. The current findings were similar to Ku and colleagues who conducted a meta-analysis and found similar results [25]. The current findings supported the conclusion of a recent meta-analysis that included only 11 studies and focused on Sudan Journal of Medical Sciences Hyder Osman Mirghani and Albaraa Altowigri the site of BMD, our study assessed additional women with osteopenia and a broad category of women without specification of menopausal status.…”
Section: Discussionsupporting
confidence: 91%
“…[15] 2018 Spain Casecontrol 14 vs 84 1.00 ± 0.12 vs 0.98 ± 0.11, lumbar 14 vs 84 0.86 ± 0.12 vs 0.84 ± 0.15, lumbar 10 years BMD was higher among women with DTC who received thyroxine for TSH suppression, no difference in BMD was observed among males compared to their counterparts without TSH suppression. The current findings were similar to Ku and colleagues who conducted a meta-analysis and found similar results [25]. The current findings supported the conclusion of a recent meta-analysis that included only 11 studies and focused on Sudan Journal of Medical Sciences Hyder Osman Mirghani and Albaraa Altowigri the site of BMD, our study assessed additional women with osteopenia and a broad category of women without specification of menopausal status.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, estrogen may provide some protection against bone loss and counteracts the resorptive effects of excess thyroid hormones in premenopausal patients with levothyroxine therapy [28]. The change of BTMs might provide an explanation for the higher BMD observed in premenopausal DTC patients than controls in this study, as well as in the above-mentioned metaanalyses [17,19]. The change of β-CTX was signi cantly different between postmenopausal DTC patients and controls, with a reduction in DTC patients and an increase in controls.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, our study suggested that TSH suppressive therapy had no adverse effects on BMD in premenopausal women. Two metaanalyses consistently reported FN-BMD and LS-BMD were signi cantly higher in patients with TSH suppressive therapy than in the control group [17,19]. The safety of TSH suppressive therapy in premenopausal women might contribute to the protective role of estrogen.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, DIO3 is expressed in osteoclasts, osteoblasts and chondrocytes, whereas DIO2 is present in mature osteoblasts making it possible to regulate TH status at the tissue level. Research in thyroidectomized postmenopausal women using L-T4 showed that biochemical euthyroidism while treated may be associated with decreased bone mineral density (Ku et al 2021). This suggests that markers involved in bone metabolism could be of interest to determine bone TH status.…”
Section: Bonementioning
confidence: 99%